A realização da noção de existência: o ensino dos verbos “ter” e “haver” numa perspectiva variacionista - Naves, Leila Regina (2018)
The present work had as its theme the study of Portuguese Language from the perspective of Educational Sociolinguistics (Cf. BORTONI-RICARDO, 2004, 2005), based on Pedagogy of Linguistic Variation (Cf. FARACO, 2008, 2015, 2017, BAGNO, 2007), with the aim of contributing to positive results in the teaching and learning of mother tongue, especially with regard to the teaching of verbs "to have" and "there is/there are" with a sense of existence, aimed at eighth grade students. The study of verbs "to have" and "there be/exist" with existential value is limited in school to the prescriptions of normative grammar, which are not always in line with the cultured norm of Contemporary Brazilian Portuguese (CBP). In this sense, we realize that the definitions and uses of these verbs that are present in didactic materials of Elementary School II do not take into account the contemporary use that CBP speakers make of these verbs, in less and more monitored contexts of the language. We understand that this approach to teaching materials increases the distance between the way in which the actual uses of the language between CBP speakers and what is prescribed in textbooks) are realized, contributing to the distance between the language in use and the language used. language that is taught in classrooms. The interest in this object of study, from a sociolinguistic perspective of language, was born from our observation of the so common and recurrent uses of the verbs "to have" and "there be/exist" with a sense of existence in which, in CBP, the verb "there be/exist" has taken on quite significantly such meaning, although most normative grammarians of the Portuguese language advise against using the verb "to have " in this sense, since the verb "to have" in the sense of "there is/exist" constitutes the reference standard of "correct use" of the so-called "standard language.". However, although we realize that such use is not currently stigmatized in speech or even in writing, prescriptive teaching based on rules that do not consider language mutability and character heterogeneous and multifaceted, reinforces the idea that such uses must be considered "wrong" and therefore avoided. In view of this, we wonder why we should avoid legitimate and authentic uses of the language teaching in favor of prescriptions that are not linked to the use of CBP and to teach our students - native speakers of this CBP - in an arbitrary way, to deny the real uses of their mother tongue, helping them to see that language as something In this sense, the present research, oriented by a sociolinguistic perspective of language, proposes a didactic intervention, composed by theoretical and applied content, related to the teaching of the notion of existence of the verbs "to have" and "there be/exist" in the written by CBP, aimed at eighth grade students of Elementary School II, in the light of the contributions of Educational Sociolinguistics, especially with regard to the Pedagogy of Linguistic Variation. After the application of our didactic proposal, we notice, in a notorious way, how much the students, when stimulated to reflect on the heterogeneity of the language and the uses that make of it, engage in the grammatical learning of the language. The teaching of the verbs "to have" and "there be/exist" with a sense of existence - a variable and non-stigmatized phenomenon in the CBP - in the light of the Pedagogy of Linguistic Variation, proved to be quite productive, contributing to the development of the communicative competence of the students participating in the research , main objective of Portuguese language teaching in Basic Education, according to the National Curricular Parameters (BRASIL, 1997, 1998).